PERAN GEREJA DALAM MENDAMPINGI KELUARGA PASCA MENIKAH DI PAROKI SANTO FRANSISKUS XAVERIUS WOLOTOPO KEUSKUPAN AGUNG ENDE - Tamelab, Petrus; Rusae, Yohanes; Te, Theresia (Pastoralia Jurnal Penelitian Dosen, 2022)
Research focuses on the problems experienced by post-marriage families. The aim of this research is to determine the role of the Church in assisting families after marriage. Building a new family through a legal marriage bond according to the Church and the state does have many obstacles and is not easy. There are many discussions about family crises marked by violence and divorce, a very strong reason is the mental attitude that rejects moral values ​​in marriage, resulting in a decline in the marriage bond. The method used in this research is a qualitative, naturalistic descriptive method. The informants for this research consisted of married couples, guardians, parents and parish priests. The research results show that the role of the Parish in assisting post-marriage families has not been implemented, despite the fact that many young families experience separation and end up in separation, the St. Francis Xaverius Wolotopo Parish has not been able to overcome developing factors such as cultural factors. This lack of awareness can be seen in the absence of work programs and follow-up support activities for post-marriage families.